Rough Writing : Ethnic Authorship in Theodore Roosevelt's America. - Taubenfeld, Aviva F. (Nation of newcomers., 2008)
As the United States struggled to absorb a massive influx of ethnically diverse immigrants at the turn of the twentieth century, the question of who and what an American is took on urgent intensity. It seemed more critical than ever to establish a definition by which Americanness could be established, transmitted, maintained, and judged. Americans of all stripes sought to articulate and enforce their visions of the nation's past, present, and future; central to these attempts was President Theodore Roosevelt. Roosevelt fully recognized the narrative component of American identity, and he calle.